Geologic e geoquímica do batólito Rapakivi Rio Branco, SW do Craton Amazônico - MT - Araújo-Ruiz, Larissa Marques Barbosa de [UNESP]; Godoy, Antonio Misson [UNESP]; Ruiz, Amarildo Salina; Sousa, Maria Zélia Aguiar de; Montano, Luiz Fernando de Mello [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2007)
The Rio Branco Rapakivi Batholith belongs to the Cachoeirinha Tectonic Domain, part of the Rio Negro-Juruena Geochronological Province located on the southwestern portion of the Amazonian Craton in Mato Grosso, Central Brasil. A systematic geological mapping on a 1:100.000 scale, coupled with petrographic and geochemical studies allowed to redefine this batholithic unit, to recognize faciological variations and to characterize the geochemical features of this rapakivi magmatism. The batholith is constituted by two major plutonic suites, the first forming a basic suite of fine-grained, equigranular, mesoto melanocratic gray to black lithotypes, with usually discontinuous porphyritic varieties located near the margins of the intrusion. The second one is characterized by acid to intermediate rocks constituted by porphyritic granites, in part granophyric, with rapakivi textures. They have K-feldspar phenocrysts of up to 4cm. Three distinct petrographic facies are recognized in this suite: 1. equigranular to pegmatitic monzogranites; 2. red rapakivi leuco-monzogranites; 3. dark red rapakivi monzogranites to quartz-monzonites. Rocks present SiO2 contents from 67% to 73%, show peraluminous to metaluminous compositions and define a high-K calc-alkaline to shoshonitic magmatism in an I- and A-type, post-orogenic to anorogenic intraplate environment. The magmatic processes are associated with the end of the collisional event that consolidated and stabilized the SW part of the Amazonian Craton.
Geology and geochemistry of the Rio Branco Rapakivi Batholith, southwest of the Amazonian Craton - MT
Keywords: Amazonian craton; Anorogenic; Geochemistry; Rapakivi; Rio Branco Batolith; batholith; calc alkaline rock; craton; facies analysis; granophyre; intraplate process; lithotype; magmatism; monzonite; petrology; phenocryst; pluton; porphyry; rapakivi; shoshonite; Amazonia; Brazil; Mato Grosso; South America